THE ORGANIZATIONAL CULTURE DIMENSIONS – THE CASE OF AN INDEPENDENT PRIVATE UNIVERSITY IN MACEDONIA - ZEQIRI, Jusuf; ALIJA, Shpresa (Studia Universitatis Babeș-Bolyai Oeconomica, 2016)
https://doi.org/10.1515/subboec-2016-0002 The objective of this study is to explore how the organizational culture as one of the most vital elements of any organization affects the success of an organization. In recent years, the organizational culture has become one of the most important areas of research. Researchers simultaneously examine the concept of organizational culture in different environments in order to develop credibility and productivity in the workplace. The effectiveness of a university and how well it operates depend, to a large extent, on how the university culture is formed. This research examines and takes in consideration the 6 Hofstede's cultural dimensions: process-oriented versus results-oriented; employee-oriented versus job-oriented; parochial versus professional; open system versus closed system, loose versus tight control, and normative versus pragmatic. The paper determines the dimensions that better represent the organizational culture of an independent private university. The study attempts to explain the effect on this university’s culture, as well as the implications in administering this system which contributes in fulfilling the mission and vision, as well as its impact in developing and realizing the strategic objectives of the university itself. JEL classification: C88